On borrowed time : the art and economy of living with deadlines - Weinrich, Harald (University of Chicago Press, 2008)
Life is short. This indisputable fact of existence has driven human ingenuity since antiquity, whether through efforts to lengthen our lives with medicine or shorten the amount of time we spend on work using technology. Alongside this struggle to manage the pressure of life's ultimate deadline, human perception of the passage and effects of time has also changed. In On Borrowed Time, Harald Weinrich examines an extraordinary range of materials--from Hippocrates to Run Lola Run--to put forth a new conception of time and its limits that, unlike older models, is firmly grounded in human experience.